NUMERICAL STUDY OF INFLUENCE OF MUTUAL SLEWIG OF ROLLER BEARING RINGS ON THE PRINCIPAL STRESSES AT CONTACT AREA - Lenka JAKUBOVIČOVÁ; Milan SÁGA; Milan VAŠKO (Scientific Journal of Silesian University of Technology. Series Transport)
Article deals with influence of mutual slewing of roller bearing rings on the principal stresses and their distribution at the contact area. Profile of rolling element is logarithmic. Roller bearing has been loaded by maximum specified load only in radial direction according to the ISO/TS 16281. In practice, the real roller bearings are not loaded only in the radial direction. Therefore, the angle alfa has been gradually slewed from alfa = 0' to 8' and equivalent principal stresses have been evaluated. This change influenced on contact conditions and contact stress distribution has changed.